Diagnostic significance of CK19, RET, galectin-3 and HBME-1 expression for papillary thyroid carcinoma. Issue 9 (19th July 2010) - Zhu, Xiaoli; Sun, Tuanqi; Lu, Hongfen; Zhou, Xiaoyan; Lu, Yongming; Cai, Xu; Zhu, Xiongzeng
Abstract : Aims: To evaluate CK19, RET, galectin-3 and HBME-1 expression in papillary thyroid carcinoma (PTC) and to evaluate their diagnostic significance. Methods: 155 PTC specimens and 83 other diseased-thyroid specimens were collected. Immunohistochemistry for CK19, RET, galectin-3 and HBME-1 was performed. Results: The 155 PTC cases were classified into eight variants according to the WHO classification, including 74 cases of classic PTC, 40 cases of papillary microcarcinoma, and rare variants. CK19, RET, galectin-3 and HBME-1 expression was 87.1% (135/155), 71.0% (110/155), 91.6% (142/155), and 95.5% (148/155), respectively, for the PTC group; expression of all these markers was much higher than that in the control group (p<0.05). However, the expression of these markers did not differ among the variants (p>0.05). The expression of these markers, particularly CK19 and RET, was diffuse and strong in the papillary structure of PTC, but weak and focal in the papilla of tissue with benign disease. The expression of CK19 in follicular PTC was significantly higher than in follicular thyroid carcinoma (FTC) (p<0.05). Conclusions: CK19, RET, galectin-3 and HBME-1 expression in PTC was higher than that in benign disease cases, but these were not specific markers for PTC. In summary, combining markers can increase the reliability and differential diagnosis of PTC. It is also worth noting that CK19 was very useful not only for the differentiation of benign and malignant papillary structure but also for the differential diagnosis of follicular PTC and FTC.